Hot electron assisted vertical leakage/breakdown in AlGaN/GaN heterostructures on Si substrates. (July 2017) - Hu, Anqi; Yang, Xuelin; Cheng, Jianpeng; Guo, Lei; Zhang, Jie; Feng, Yuxia; Ji, Panfeng; Tang, Ning; Ge, Weikun; Wang, Xinqiang; Shen, Bo
Abstract: We present a hot electron assisted vertical leakage/breakdown mechanism in AlGaN/GaN heterostructures on Si substrates by a combination of applying vertical and lateral bias conditions. Beyond a critical bias point, the vertical leakage current under the combined bias condition is larger than that under a pure vertical bias condition which results in a lower breakdown voltage. The critical bias has a positive temperature dependence. A model is proposed that highly energetic hot electrons can release trapped electrons from defects and even ionize them. The model is proved by investigating the detrapping and ionization mechanisms by changing hot electron energy. Highlights: The high energetic hot electrons can assist vertical leakage and even accelerate vertical breakdown. A model is proposed that high energetic electrons can detrap or ionize defect states. The trap states which are responsible for the phenomenon are identified.